Am I (Deep) Blue? Music-Making AI and Emotional Awareness - Novelli, Nicholas; Proksch, Shannon (Frontiers in Neurorobotics, 2022)
Artificial Intelligence has shown paradigmatic success in defeating world champions in strategy games. However, the same programming tactics are not a reasonable approach to creative and ostensibly emotional artistic endeavors such as music composition. Here we review key examples of current creative music generating AIs, noting both their progress and limitations. We propose that these limitations are rooted in current AIs lack of thoroughly embodied, interoceptive processes associated with the emotional component of music perception and production. We examine some current music-generating machines that appear to be minimally addressing this issue by appealing to something akin to interoceptive processes. To conclude, we argue that a successful music-making AI requires both the generative capacities at which current AIs are constantly progressing, and thoroughly embodied, interoceptive processes which more closely resemble the processes underlying human emotions.